Intervention during the Perinatal Period: Synthesis of the Clinical Practice Guidelines from the French National College of Midwives. (8th December 2022) - Barasinski, Chloé; Zaros, Cécile; Bercherie, Julie; Bernard, Jonathan Y.; Boisseau, Nathalie; Camier, Aurore; Chanal, Corinne; Doray, Bérénice; Dugravier, Romain; Evrard, Anne; Ficheux, Anne‐Sophie; Garlantézec, Ronan; et al.
Abstract: These clinical practice guidelines from the French National College of Midwives (CNSF) are intended to define the messages and the preventive interventions to be provided to women and co‐parents by the different professionals providing care to women or their children during the perinatal period. These guidelines are divided into 10 sections, corresponding to 4 themes: 1/ the adaptation of maternal behaviors (physical activity, psychoactive agents); 2/ dietary behaviors; 3/ household exposure to toxic substances (household uses, cosmetics); 4/ promotion of child health (breastfeeding, attachment and bonding, screen use, sudden unexplained infant death, and shaken baby syndrome). We suggest a ranking to prioritize the different preventive messages for each period, to take into account professionals' time constraints.